Partial Egalitarianism And Marital Instability: The Role Of Ambivalent Gender Ideology In Driving Latent Conflict Among Javanese Couples, Indonesia - Iwan Zaenul Fuad; Mohammad Fateh; Anindya Aryu Inayati; Agung Barok Pratama; Anis Ni'am Imana (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2026)
The gender roles played by husbands and wives have considerable impacts on the stability of marriage. However, marital instability can lead to divorce. Egalitarian (nontraditional) gender roles cause negative effects on marital stability. This research tried to reveal the perception of married couples in Java about their gender roles, whether egalitarian or traditional. This study found the fact that in general, husband and wife who become respondents tend to choose egalitarian (non-traditional) gender roles, even though in three aspects they still adhere to the patriarchal (traditional) gender role, most of them reject the concept of: (a) household leadership based on agreement (not on sex); (b) the possibility of providing cost of living from wife to husband; and (c) household expenses are shared responsibility. Moreover, the egalitarian gender perception of the respondents has negative impact on marital stability. Fortunately the impact is not significant.